Pomegranate Cultivars with Diverse Origins Exhibit Strong Resistance to Anthracnose Fruit Rot Caused by Colletotrichum gloeosporioides, a Major Disease in Southeast United States - Alexander Schaller; John M. Chater; Gary E. Vallad; Jeff Moersfelder; Claire Heinitz; Zhanao Deng (Horticulturae, 2023)
Pomegranate, a pivotal fruit that is well recognized globally and a rapidly emerging crop in the southeastern United States and other subtropical regions, faces a formidable challenge from Colletotrichum spp., a fungal pathogen causing anthracnose fruit rot, which leads to severe to complete premature fruit drop. The development and use of disease-resistant cultivars are considered the most cost-effective and sustainable approach to managing this disease. Identifying sources of resistance is essential for developing new cultivars with improved resistance to this disease. This project aimed to expand the scope of evaluation through a 2-year field study in central Florida, examining fruit from 35 cultivars from diverse origins using both artificial inoculation at the petal dehiscent stage and natural infection. Lesion size on the fruit was measured during the growing season in a field setting. Subsequently, seven cultivars were selected for further testing by inoculating detached mature fruit and measuring lesion size to confirm observed resistance and determine the correlation between resistance observed in planta in the field and on detached fruit in the laboratory. The field study revealed significant genetic differences among pomegranate cultivars in susceptibility to naturally occurring and induced anthracnose fruit rot and classified cultivars into five resistance or susceptibility classes. Five cultivars that originated from different regions of the world, including ‘Azadi’, showed consistent resistance to anthracnose fruit rot in the field. Resistance remained strong on detached mature fruit. A strong positive correlation existed between resistance levels on in-planta fruit and on detached mature fruit, suggesting a possible simple, efficient approach to screening breeding populations for anthracnose fruit rot resistance in pomegranate. These findings represent an important step toward developing new anthracnose-resistant cultivars and understanding and improving disease resistance in this increasingly important fruit crop in the world.